Clinical proteomics in gastrointestinal cancers - Metzger, Jochen (Henry Stewart Talks, 2013)
Detection of cholangiocarcinoma in patients with biliary strictures of unknown origin, Cholangiocarcinoma surveillance in patients with primary sclerosing cholangitis, Differentiation of pancreatic carcinoma from chronic pancreatitis, Elucidation of underlying pathological mechanisms in pancreatic cancer